How hotel companies can foster customer sociability behaviour on Facebook? - Vaičiukynaitė, Eglė; Gatautis, Rimantas (Journal of Business Economics and Management, 2018)
Social network sites (hereinafter, SNSs) have become extremely popular, playing an important role in consumers’ every day lives. Empowered by SNSs, the customer becomes more active and spends more time with their family, friends or companies online. Therefore, companies seek to encourage online conversations for several beneficial reasons such as maintaining relationships with their customers and achieving customer loyalty. There are no widely accepted characteristics of company messages that foster customer sociability behaviour regarding likes, comments, shares and emotion expressions on Facebook in literature. The purpose of this paper is to explore the characteristics of company messages that facilitate customer sociability behaviour on Facebook. The current study integrates content analysis and text analysis with the Linguistic Inquiry and Word Count Software (LIWC). The data were obtained from two five-star hotel brands on Facebook from 18th October 2016 to 18th October 2017. A total of 306 messages were collected. The results indicated that social messages generated more consumer likes, comments and emotional expressions on Facebook. The number of likes, comments and emotion expressions can be facilitated by images with humans. Messages accompanied with social words exhibit customer comments and emotion expressions.